A Comparative Study Of Quality Of Life Between Iranian And Malaysian Postgraduate Students - Vakili, Sara (2013)
Quality of Life (QOL) is a highly important concept because of its mediating impact on mental health. Therefore, the aim of this study is to investigate the quality of life (QOL) between Iranian and Malay Malaysian postgraduate students. A total of 370 postgraduate students whom are 185 Iranian and 185 Malay Malaysian postgraduate students were randomly picked up as samples in this study. An instrument of WHOQOL-BREF questionnaire was administered in the pre and post-test. The instrument consists of 26 questions divided into four main domains, i.e. physical health, psychological health, social relationship, and environment. Besides, a semi-structured interview was employed to six samples, three male and three female. Sample characteristics were determined using means, standard deviation, and independent t-tests to consider differences for the QOL domain in the two groups of the postgraduate students. The finding indicated that the total QOL measures among Iranian and Malay Malaysian postgraduate students are significantly different (63.11 ± 10.04 and 66.20 ± 8.13, respectively). Apart from the physical health and social relationship domains, all the other domains were significantly different between the two groups. Among the postgraduate students, the scores of QOL on global health and psychological health among Iranians were higher than those of Malays (P<0.001), but the scores in the environment domain were higher for the Malays.